Clinical and epidemiological significance of stress-induced impact of psychotraumatic factors of the war in Ukraine and the COVID-19 pandemic on the development of pathological changes in the cardiovascular system in children - D.S. Bardas; I.O. Mityuryayeva-Kornijko (Zdorovʹe Rebenka, 2025)
Cardiovascular diseases (CVD) remain one of the leading causes of morbidity and mortality worldwide. At the same time, they are increasingly emerging as a consequence of adverse factors inherent in childhood. Epidemiological research data confirm that critical periods of early development, in particular the influence of socio-economic disadvantage and psychological stress, are of decisive importance for the formation of CVD risk in adulthood. In recent years, Ukraine has been experiencing prolonged periods of crisis, in particular military conflicts and the COVID-19 pandemic. These circumstances significantly affect the socio-economic status of families and the health of children. According to Bürgin et al. (2023), living in a conflict zone and forced migration have far-reaching consequences for the psychosocial and physical health of children, creating additional risks of developing chronic pathologies, in particular CVD. Despite the significant body of evidence linking childhood trauma to adult disease, the role of psychosocial factors in childhood remains poorly understood in terms of their contribution to cardiovascular disease, particularly pathophysiological mechanisms such as neuroendocrine activation, epigenetic programming, metabolic abnormalities, and vascular dysfunction.